Iraq Systematic Country Diagnostic - World Bank Group (World Bank, Washington, DC, 2017)
This systematic country diagnostic for Iraq identifies the three characteristics that underlie Iraq’s predicaments: its poor governance, dependence on oil wealth, and ethnic and regional diversity. It posits that the combination of oil wealth and ethnic and religious fragmentation has led to conflict, violence, and fragility due to long-standing governance problems and the inability of institutions to ensure an equitable allocation of resources among the country’s population and regions. Systematic country diagnostic reports are a product of the World Bank Group and reflect consultations with the national authorities, civil society, the private sector, and other stakeholders. The report is organized as follows: section one gives introduction. Section two lays out the country context of Iraq and discusses the three characteristics noted above (poor governance, dependence on oil wealth, and ethnic and regional diversity) that have led to Iraq’s fragility, conflict, and violence. Section three discusses the main features of poverty and exclusion in Iraq, while section four presents the key challenges facing the country and their relation to the three identified characteristics. Section five discusses social, economic, and environmental sustainability, and section six concludes with a prioritization of these constraints in the context of tensions or tradeoffs that are inherent to Iraq’s social and economic realities.